Neem hinders pollination - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Many people sing the praises of the neem tree, partly because of its insect repellent constituents. Rightfully so. However, its growing popularity is causing problems for fruit farmers with neem in the vicinity. Its insect repelling component...